PENGARUH KEPERCAYAAN, KEAMANAN, RISIKO, DAN LIFESTYLE TERHADAP MINAT DALAM MENGGUNAKAN LAYANAN E-BANKING - Ayu Wahyu Cahyaningtyas; Banu Witono (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
This study aims to determine the Effect of Trust, Security, Risk, and Lifestyle on Interest in Using E-banking. Thisresearch was conducted on students at the University of the city of Surakarta. This type of research is quantitative, the sampling technique is purposive sampling and the research data is primary data, data collection is done by distributing questionnaires. The results of this study indicate that trust and lifestyle have an effect on interest in using E-banking, while security and risk have no effect on interest in using E-banking. The implications of this research: (1) It is relevant for banks to pay attention to the trust and lifestyle factors in developing E-banking in the banking transaction system. (2) It is necessary to pay attention to security and risks in influencing interest in using E-banking.